The regulatory effects of serum catecholamines and endothelial cells in pig hemorrhagic shock and fluid resuscitation models - Xiaoli Zhao; Wei Yuan; Shuo Wang; Junyuan Wu; Chunsheng Li (Resuscitation Plus, 2024)
Background: Acute blood loss not only leads to systemic compensatory response, but also the induced changes in vascular endothelial function.These pathological changes may have potential compensatory significance for maintaining organ perfusion and fluid resuscitation. Objective: To understand trauma-induced endotheliopathy and their compensatory roles in acute hemorrhage, a porcine model of hemorrhagic shock (HS) was used to evaluate changes in vascular endothelial factors and catecholamine levels at different time points from shock to fluid resuscitation. Methods: HS was induced in female pigs by rapid bleeding via the arterial sheath. Hemodynamic monitoring was performed using a pulse index continuous cardiac output (PiCCO) system in HS and fluid resuscitation. Femoral vein blood samples were collected at baseline and 40% mean arterial pressure (MAP, shock), MAP recovery, and 30 min, 1 h, and 2 h after recovery. Serum levels of catecholamine and Angiopoietin-1 (Ang-1), Angiopoietin-2 (Ang-2), Tie-2, Eselectin, intracellular adhesion molecule-1 (ICAM-1), soluble thrombomodulin (sTM), and Syndecan-1 (SDC-1) were evaluated using enzyme-linked immunosorbent assay (ELISA). Results: Serum catecholamine levels were significantly higher in the shock than in the baseline state. Ang-1 and Ang-2 are endothelial growth factors secreted with distinct roles. Ang-1 stabilizes the endothelium and inhibits vascular leakage, and Ang-2 has the opposite effect. The ratio of Ang-2/Ang-1 was significantly higher in the shock state than in the baseline state; however, the Ang-1/Tie-2 ratio was comparable between the two states. This suggests that changes in vascular permeability may mainly depend on the upregulation of Ang-2 function. Serum levels of E-selectin, ICAM-1, sTM, and SDC-1 were significantly higher in the shock state than in the baseline state. After the MAP was restored to the baseline state, the levels of E-selectin, and SDC-1 remained higher compared with the baseline state until 1 h after MAP recovery. Conclusions: serum levels of catecholamines and vascular endothelial markers increased transiently under HS, promoting a compensatory response of the circulatory system to acute bleeding. This may be one of the potential theoretical basis for restrictive fluid resuscitation.